"Sky Full of Stars" Pattern: Dermoscopic Findings in a Desmoplastic Giant Congenital Melanocytic Nevus. Issue 3 (27th February 2017) - Martín‐Carrasco, Pablo; Bernabeu‐Wittel, José; Dominguez‐Cruz, Javier; Zulueta Dorado, Teresa; Conejo‐Mir Sanchez, Julian
Abstract: Desmoplastic giant congenital melanocytic nevus (DGCN) is an uncommon variant of congenital nevus, presenting as a progressive induration and hypopigmentation of the lesion that occasionally causes hair loss and even total or partial disappearance of the nevus. A 6‐month‐old girl with a giant congenital melanocytic nevus that involved the entire posterior side of the right thigh was seen in our department. Nine months later, the peripheral area of the nevus presented as a marked induration with hypopigmentation. Dermoscopy demonstrated a reticular pattern exclusively located in the perifollicular areas, with a radial distribution from the follicular ostium that mimicked a "sky full of stars." We report a case of DGCN, including a dermoscopic description of the findings noted in the indurated and hypopigmented areas that appear as a "sky full of stars" image.